2022
DOI: 10.3892/ijo.2022.5431
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‑1 binds GRP78 to promote the proliferation and metastasis of gastric cancer

Abstract: The present study aimed to investigate the potential molecular mechanisms by which galectin-1 (Gal-1) and glucose-regulated protein 78 (GRP78) influence the development of malignant gastric cancer (GC). Immunohistochemistry and western blotting were used to map the expression and location of the Gal-1 gene in the 80 paraffin-embedded GC samples, 16 fresh samples and surrounding tissues. Gal-1 was overexpressed and knocked down using lentiviral vectors in the human GC cell lines HGC-27 and AGS. Through the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Considering its most significant aberrant expression in vitro , we further focused on its functions and finally found that si-LGALS1 could inhibit the cell migration and invasion ability of KIRC, which might be involved in suppressing EMT process. Numerous studies have provided the consistent findings that it functioned as a tumor promoting factor in multiple cancers, such as in gastric cancer ( Zhang et al, 2022 ) and ovarian cancer ( Li et al, 2023b ). Collectively, all above evidences have directly or indirectly supported our findings, providing potential clues regarding the prognostic value of our EMT related signature of KIRC.…”
Section: Discussionmentioning
confidence: 94%
“…Considering its most significant aberrant expression in vitro , we further focused on its functions and finally found that si-LGALS1 could inhibit the cell migration and invasion ability of KIRC, which might be involved in suppressing EMT process. Numerous studies have provided the consistent findings that it functioned as a tumor promoting factor in multiple cancers, such as in gastric cancer ( Zhang et al, 2022 ) and ovarian cancer ( Li et al, 2023b ). Collectively, all above evidences have directly or indirectly supported our findings, providing potential clues regarding the prognostic value of our EMT related signature of KIRC.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, previous investigations indicated that certain host factors such as HSPG, GRP78, and ATP5B were involved in the cell entry of HEV [ 31 ]. Moreover, GRP78 and ATP5B were expressed in normal gastric tissue and were good prognostic factors of gastric cancer according to the HPA (Human Protein Atlas) database and previous reports [ 32 , 33 ]. Thus, we have rationale to speculate that HEV infects gastric tissue by binding to receptors such as GRP78 and ATP5B and contributes to gastric cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…DnaJ Heat Shock Protein Family (Hsp40) Member B11 (DNAJB11), a co-chaperone of HSPA5/BiP/GRP78 ( 33 ), was reported to promote the development of pancreatic cancer cells in vitro and in vivo by upregulating the HSPA5 expression and activating EGFR/MAPK pathway ( 34 ). Galectin−1, a small protein family member with an affinity for β-galactosides ( 35 ), was reported to bind HSPA5 to promote the proliferation and metastasis of gastric cancers in vitro and in vivo ( 36 ). Leucine zipper EF-hand-containing transmembrane protein-1 (LETM1) was disclosed to have its genomic deletions in Wolf–Hirschhorn syndrome (WHS) and revealed to regulate ion homeostasis, cell viability, mitochondrial morphology, as well as overexpression in different human cancers.…”
Section: Hspa5 In Cancersmentioning
confidence: 99%